Synthesis , Characterization and Biological activity of new derivatives of Chromen-2-one - Behrami, Aziz (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
We report the organic syntheses of new derivatives from Chromen-2-one and their antibacterial activity. Compounds 4-[Acetyl-(2-oxo-2H-chromen-4-yl)-amino]- benzenesulfonyl chloride 1a, 4-[Acetyl-(2-oxo-3-phenylsulfamoyl-2H-chromen-4-yl)-amino]-benzenesulfonyl chloride 2a , 2-{4-[Acetyl-(4-chlorosulfonyl-phenyl)-amino]-2-oxo-3-phenylsulfamoyl-2H-chromen-7-ylamino}-benzoic acid 3a. All Structures have been synthesized and characterized using melting points , IR spectra , 1H-NMR, 13C-NMR spectra , and elemental analyses . The purified synthesized compounds (1a,2a,3a), at contcentrations 2,3,5 mg/ml was tested for their antibacterial activity against three bacterial cultures ;Staphylococcus aureus, Escherchia coli and Bacillus cereus. The antibacterial activity of synthesized compounds are compared with antibacterial activity of standard antibiotics cephalexine and streptomycine. The compounds (1a,2a,3a) shows different bacteriostatic and bacteriocidal activity.